Biosorption of Basic Yellow 28 dye onto watermelon seeds. Part II: modeling and optimization by response surface methodology - Saida Benkaddour; Imane El Ouahabi; Mohamed Essoufy; Hasnaa Hiyane; Nour-eddine Lazar; Hamid Saufi; Rachid Slimani; Noha F. Shalaby; Yassine Riadi; Sherif A. Abdel-Gawad (Green Chemistry Letters and Reviews)
The powder of treated watermelon seeds (WST), obtained through hexane extraction, has proven to be a promising adsorbent for the environmentally friendly and cost-effective removal of Basic Yellow 28 (BY28) using adsorption techniques. By optimizing conditions through Central Composite Design (CCD), focusing on key factors such as temperature, adsorbent weight, and dye concentration, we aimed to enhance the efficiency of the adsorption process. Our study assessed the accuracy of the model and regression coefficients through analysis of variance (ANOVA). The results revealed a strong agreement between the predicted values derived from the model and the experimental values for BY28, with a coefficient of determination (R2) equal to 0.92, indicating a high level of reliability and effectiveness of the developed model in predicting the adsorption behavior of BY28 on WST. Under optimal conditions, including a temperature of 35°C, an adsorbent weight of 2.45 g/L, and a dye concentration of 50 mg/L, the adsorption process demonstrated exceptional efficiency. This study highlights the remarkable potential of treated watermelon seeds for the removal of organic pollutants, emphasizing the importance of using sustainable and readily available agricultural materials for environmental remediation, thus contributing to both environmental conservation and cost-effectiveness in wastewater treatment processes.